Pengembangan Ekonomi Lokal melalui Budidaya Rumput Laut sebagai Sumber Pendapatan Masyarakat - Wilda Fatmala; Murni Sari; Yunarsi Yunarsi; Novitasari Rahman (Universitas Proklamasi 45, 2023)
Local economic development through seaweed cultivation in Kapuntori District, Buton Regency is very promising and profitable so it is necessary to make maximum efforts so that problems that arise in the development of seaweed cultivation can be resolved. This study aims to determine income, assess the feasibility of seaweed farming as a source of income for the people of Wawoncusu Hamlet, Lambusango Village, Kapuntori District, Buton Regency, and at the same time develop a strategy for developing a seaweed cultivation business. This study uses a descriptive research method with a qualitative approach. The data source is primary data which includes information from farming about costs, revenues, and income of farming and development strategies that have been carried out by farming businesses, while secondary data includes data documentation. Data collection methods and techniques used interview, observation, and documentation methods, while data analysis methods used a qualitative descriptive approach. Based on the results of the analysis obtained information that the average income of seaweed farmers for 40 days obtained from 1 unit raft is Rp 2,200,000. The feasibility of seaweed farming shows the R/C ratio >1, namely 5.11 and 2.39. If the R/C Ratio >1, then the seaweed business is efficient and profitable. The most effective strategy for seaweed development in Wawoncusu Hamlet, Lambusango Village, Kapuntori District, Buton Regency is SO and WT analysis.